Probing the penicillin sidechain selectivity of recombinant deacetoxycephalosporin C synthase. - Dubus, A; Lloyd, MD; Lee, H; Schofield, C; Baldwin, J; Frere, J (2001)
Deacetoxycephalosporin C synthase from Streptomyces clavuligerus catalyses the conversion of the five-membered penicillin ring to the unsaturated six-membered cephem ring of deacetoxycephalosporin C. The effects on enzyme activity of the penicillin substrate sidechain and various cofactors were investigated using a continuous spectrophotometric assay. The conversion of penicillin G to phenylacetyl-7-aminodeacetoxycephalo sporanic acid (G-7-ADCA) was confirmed, and further details of the reaction were elucidated. The conversion of ampicillin to cephalexin was faster than that of acetyl-6-APA to acetyl-7-ADCA kcat = 0.120 +/- 0.001 s(-1) versus 0.035 +/- 0.001 s(-1), but they had similar Km values: 4.86 +/- 0.12 and 3.28 +/- 0.26 mM, respectively. Amoxycillin and penicillin V were also converted at low levels. Conversion was not detected for penicillanate, 6-aminopenicillanate, carbenicillin, temocillin, ticarcillin or benzylpenicilloic acid, suggesting that the enzyme has a relatively strict selectivity for the sidechain of the penicillin substrate.